2003
DOI: 10.1002/rcm.1213
|View full text |Cite
|
Sign up to set email alerts
|

Parallel determination of multiple protein metabolite interactions using cell extract, protein microarrays and mass spectrometric detection

Abstract: Analysis of interactive networks between proteins and other molecular constituents is of paramount importance to delineate complex cellular processes. In order to facilitate this process, new technologies that allow rapid, high-throughput parallel screening, as well as identification of constituents, are necessary. A particularly powerful combination in this regard could be the use of multiprotein microarrays coupled with mass spectrometry (MS). In the initial step of the method development we applied MS to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…This low molar ratio is optimized for stabilization of native interactions, efficient affinity isolation, and minimal interference with MS readout. Although glutaraldehyde has been widely used for stabilization purposes in electron and optical microscopy (5,30,32,60,61), it has been seldom used with MS in the cellular context, and in these cases, it has been used largely for visualization of low molecular mass metabolites (62). Indeed, in the MS context, glutaraldehyde has often been considered detrimental (63).…”
Section: Resultsmentioning
confidence: 99%
“…This low molar ratio is optimized for stabilization of native interactions, efficient affinity isolation, and minimal interference with MS readout. Although glutaraldehyde has been widely used for stabilization purposes in electron and optical microscopy (5,30,32,60,61), it has been seldom used with MS in the cellular context, and in these cases, it has been used largely for visualization of low molecular mass metabolites (62). Indeed, in the MS context, glutaraldehyde has often been considered detrimental (63).…”
Section: Resultsmentioning
confidence: 99%
“…2. Several additional studies have also found that multiple metabolites interact with a protein [2,7], suggesting this pattern may be prevalent. These unexpected metaboliteprotein interactions add both complex and novel regulatory controls into protein networks [13].…”
Section: Metabolite Regulation Of Protein Function Is Diversementioning
confidence: 92%
“…What fraction of the proteome interacts with metabolites is unknown.test group including protein kinases and other enzymes bind to at least one hydrophobic metabolite [6], that four out of nine tested proteins bind to at least two hydrophilic metabolites [2], and that 85% of 172 proteins with a lipid-binding domain bind to a lipid molecule [7]. It is reasonable to postulate that many proteins, if not the majority, interact with one or more metabolites.…”
Section: Metabolite-protein Interactions Are Extensivementioning
confidence: 98%
See 1 more Smart Citation
“…Morozov et al [8][9][10][11] deposited proteins by the ESD technique for protein microarrays and reported that the deposited proteins retained their biological properties. Protein films of a-lactalbumin were also deposited on poly(ethylene terephthalate), which was coated with aluminum, by the ESD technique.…”
Section: The Electrospray Deposition (Esd) Methods Is a Technique Thatmentioning
confidence: 99%